Synthesis, Characterization and Enzyme Inhibition Activity of Organophosphorus Trichalcones Containing Core-Phosphate Moiety - Khapate, Sunil R.; Wankhede, Dnyaneshwar S.; Deshpande, Anitha S.; Khillare, Neeta S.; Khandagale, Anil (Asian Journal of Chemistry, 2019)
Facile synthesis of various organophosphorus trichalcones, possessing substantial insecticidal activity, by using tris(4-acetylphenyl)-phosphate (3) and substituted benzaldehydes as a precursor has been reported. Key precursor 3 has been prepared under mild conditions in presence of tetrabutylammonium bromide (TBAB) as a phase transfer catalyst. All the synthesized compounds (5a-h) were screened for their antibacterial activity and inhibition of α-amylase of insect pest, Tribolium castaneum (Herbst) (Coleoptera: Tenebrionadeae). Biological activity evaluation study revealed that among all the compounds screened, compound 5g found to have promising inhibition of α-amylase of insect pest, Tribolium castaneum. All the synthesized compounds revealed insignificant antimicrobial activity against pathogenic bacteria even at 500 μg/mL.